Digital Training in Building Chatbot-based Online Learning Media: Action Research for Teachers in Semarang City through the "Train The Teachers" Training - Dewi, Devana Afriani; Julia, Julia; Jonathan, Christian (Mimbar Sekolah Dasar, 2022)
The lack of student learning motivation and teacher difficulties in monitoring student learning progress is considered to be the main problems in distance learning, especially during the COVID-19 pandemic. This research employed action research methods by involving 20 teachers in several elementary schools in Semarang City spread across several sub-districts. The research results obtained: First,  six steps to determine the increase in teacher creativity and understanding, namely the introduction of chatbot and chatbot templates as digital learning media in schools; the implementation of the first training session; the assignment of creating and designing chatbots from templates; the implementation of the second training session and finale chatbot feedback. Second, during digital chatbot training, Acita template was used to see an increase in teacher creativity and understanding of chatbots. The result revealed that, in the aspect of teacher creativity, the point of chatbot design creativity had increased by 41%, creativity in material integration had increased by 46%, and interactive creativity in chatbots had increased by 33%. In addition, in the aspect of teacher understanding, the points of understanding of chatbot structure and understanding of chatbot development had increased by 47%.